2017
DOI: 10.15540/nr.4.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Choices Influence Brainwave Activity: Single Case Study of a 12-year-old Female

Abstract: Research into the benefits of children eating breakfast has previously focused on educational and cognitive performance as well as behavior. Few nutritional investigations have utilized brain imaging technology in order to examine how breakfast influences brain function.This single case study used quantitative electroencephalography (qEEG) in order to assess how three different breakfast choices affected a 12-year-old female's brainwave activity. The three different breakfast conditions included no breakfast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A 2012 study in Australian school students found a significant association between habitual breakfast type consisting of carbohydrates and proteins and literacy scores [ 56 ]. Similarly, a case study done on a 12-year-old girl indicated that while skipping breakfast and consumption a carbohydrate-rich breakfast of high-sugar cereals increased high-beta brainwave activity associated with anxiety and focus issues, a balanced breakfast of proteins and carbohydrates normalized the high-beta activity [ 57 ]. However, it is important to note that although meats and eggs offer nutritional sources of protein, we did not see similar results in children who consumed soy or dairy products, which are also rich sources of protein, which suggests a potential benefit of animal-based protein sources which are often higher in fats.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study in Australian school students found a significant association between habitual breakfast type consisting of carbohydrates and proteins and literacy scores [ 56 ]. Similarly, a case study done on a 12-year-old girl indicated that while skipping breakfast and consumption a carbohydrate-rich breakfast of high-sugar cereals increased high-beta brainwave activity associated with anxiety and focus issues, a balanced breakfast of proteins and carbohydrates normalized the high-beta activity [ 57 ]. However, it is important to note that although meats and eggs offer nutritional sources of protein, we did not see similar results in children who consumed soy or dairy products, which are also rich sources of protein, which suggests a potential benefit of animal-based protein sources which are often higher in fats.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons that interact with each other can transmit vibrations and information that result in brain waves, which are divided into several types based on frequency and depending on the psychological or mental state of the individual, with proper nutrition and regular physical activity stimulation. A balanced and nutritious diet can help maintain optimal brain function (Maclrney et al, 2017).…”
Section: Introductionmentioning
confidence: 99%